1994
DOI: 10.1007/bf01987642
|View full text |Cite
|
Sign up to set email alerts
|

Heparins as essential antioxidants

Abstract: Abstract. Chronically inflamed tissues contain significant concentrations of oxygen radicals, possibly generated by transition metal species such as Fe(II) and Cu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Although heparin is able to block voltage-gated Ca# + channels [48,49], we have previously ruled this out as a means of suppressing c-fos induction [13], and in the present study further discount this possibility by using an ionophore to circumvent channel-dependent entry. Heparin chains can act as scavengers of oxygen radicals [50,51], and could conceivably alter radical-dependent signal-transduction pathways [52] by scavenging diffusible radicals at the cell surface. However, catalase and superoxide dismutase were without effect on c-fos induction by ionomycin (T. Miralem and D. M. Templeton, unpublished work).…”
Section: Discussionmentioning
confidence: 99%
“…Although heparin is able to block voltage-gated Ca# + channels [48,49], we have previously ruled this out as a means of suppressing c-fos induction [13], and in the present study further discount this possibility by using an ionophore to circumvent channel-dependent entry. Heparin chains can act as scavengers of oxygen radicals [50,51], and could conceivably alter radical-dependent signal-transduction pathways [52] by scavenging diffusible radicals at the cell surface. However, catalase and superoxide dismutase were without effect on c-fos induction by ionomycin (T. Miralem and D. M. Templeton, unpublished work).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that scavenging of H 2 O 2 , an inhibitor of phosphatases (59), suppressed platelet-derived growth factor signaling (60), possibly by decreasing the level of phosphorylated signaling intermediates. Heparin chains can act as scavengers of oxygen radicals (61,62) and might conceivably alter signal transduction pathways by scavenging diffusible oxygen radicals at the cell surface. However, heparin failed to affect endothelin-induced contraction in our cultures, an event dependent on Ca 2ϩ release and myosin light chain kinase activation, 2 arguing against such a general effect.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that GSH-Px activity was significantly reduced in the sham group compared to PTX and heparin groups. It has been reported here that GSX-Px increase in heparin and PTX groups shows that heparin can act as synergistic endogenous antioxidants with other free radical inhibitors [25,41]. Pentoxifylline is a powerful free radical scavenger and has a reducing effect on superoxide release and neutrophil degranulation [29].…”
Section: Discussionmentioning
confidence: 78%
“…It is observed that antioxidant application reduced the severity and degree of adhesions after intestinal ischemia in rats [1]. Thus, it has been reported that heparin can act as a synergistic endogenous antioxidant with other free radical inhibitors [25,41]. PTX is a potent free radical scavenger and has a reducing effect on superoxide release and neutrophil degranulation [29].…”
Section: Discussionmentioning
confidence: 99%